OBSTRUCTIVE APNEA SYNDROME IN SLEEP: A MODERN LOOK AT DIAGNOSTICS AND TREATMENT - Khamidjonov , Sh.; Khodjanov , Sh.; Akhundjaov , N. (EurasianUnionScientists, 2021)
Obstructive sleep apnea syndrome (OSA) is a violation of breathing during sleep as a result of the closure of the upper airways, leading to a partial or complete cessation of air supply, the onset of hypoxia, and as a result, a transient decrease in the depth of sleep, followed by restoration of patency of the upper airways and air intake [1,2]. During a patient's sleep, such episodes can occur hundreds of times per night, which in the presence of clinical symptoms is called OSAS syndrome or obstructive sleep apnea-hypopnea syndrome [3].